Effect of multiple treatment of cattle with diminazene aceturate on the infectivity and transmissibility of drug-resistant Trypanosoma congolense for Glossina morsitans centralis - Diack, A.; Moloo, S.K.; Peregrine, A.S. (1998)
Six Boran cattle were infected with the drug-resistant Trypanosoma congolense IL 3338. At the first peak of parasitemia different groups of 200 teneral Glossina morsitans centralis were fed once on each animal, just prior to treatment with diminazene aceturate at a dose of 3.5 mg kg-1 body weight (b.w.). thereafter, all animals were monitored three times a week and retreated with the same drug dosage whenever the packed red blood cell volume (PCV) declined in three consecutive samples from one or more of the animals. After eight treatments at approximately two-week intervals the mean duration when parasites were not detected after each treatment did not increase, but remained at 7.8 (+ or -) 1.1 days. the mean PCV declined from 33.2 (+ or -) 0.6 percent at the time of the first treatment to a mean inter-treatment value of 23.7 (+ or -) 2.6 percent between the eighth at ninth treatment. Therefore, subsequent to the eighth treatment diminazene aceturate was administered as before but at a dose of 7.0 mg kg-1 b.w. After treatment with this higher dosage the mean inter-treatment PCV increased from 25.4 (+ or -) 2.4 percent following the first treatment to 32.9 (+ or -) 1.7 percent for the two-month period following the fifth treatment. At least 14 days after treatments with diminazene aceturate at 3.5 mg kg-1 b.w., and 30 days after treatments at 7.0 mg kg-1 b.w., similar numbers of flies as used for the first feed were fed on one occasion on each animal. Thereafter, 10 flies with mature infections from each group were fed individually on mice to determine the transmissibility index. In general, the midgut and hypopharynx infection rates in flies of all groups were not significantly lower than that of the control grouHowever, while tsetse groups that fed following the second and third treatments with diminazene aceturate at 7.0 mg kg-1 b.w. picked up infections from all six cattle, flies fed following the fourth treatment became infected from only two of the six animals. Thus, repeated treatment with diminazene aceturate at a dose of 7.0 mg kg-1 b.w. resulted in the apparent complete elimination of infection in four out of six animals. In contrast, the transmissibility index of T. congolense IL 3338 was not affected by multiple treatment with diminazene aceturate.